Studi Awal Bioekologi Ikan Geso (Hemibgrus wyckii, Bagridae) - Aryani, Netti; Hasibuan, Saberina (Jurnal Perikanan dan Kelautan, 2016)
Nowadays, geso fish Hemibagrus wyckii Bagridae is extinction The objective of this research is to analyze the distribution of length and weight of Geso fish, water quality parameter as the characteristic of Geso habitat and reproduction aspect which is the basic data to perform the domestication process. To know the distribution of length and weight of Geso fish, the samples were taken from three research locations, namely Kampar Kanan River, Kampar Kiri River and Koto Panjang Reservoir, each with 15 individual, To analyze the reproduction aspect of Geso fish required 45 samples and to get the data of Geso fish habitat characteristic was taken once monthly water samples in June, July and August 2015 in three research sites, Kampar Kanan River, Kampar Kiri River and Koto Panjang Reservoir. The results showed that the average length of total and weight of geso fish from Kampar Kanan River (491.93 mm, 1390.83g) and Kampar Kiri River (489.73 mm, 1338.97g) was higher than that of Koto Reservoir Length (286.60 mm; 1078 g). The water quality parameters that are the main differentiator between the three habitats are nitrite, nitrate, electric conductivity and COD. Fecundity of geso fish ranges from 2943-9558 eggs with egg diameter ranging from 1.04 to 2.81 mm. Gonad Somatik Index (IGS) of geso female fishingTKG IV between 2.73-3.97%and males between 1.22-2.00%.